2014
DOI: 10.1007/s10517-014-2555-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antenatal Hypoxia on Tissue Homeostasis in the Myocardium of Albino Rats: Early and Delayed Consequences

Abstract: Body weight, absolute and relative heart weight, DNA-synthetic activity of cardiomyocytes, and number of nucleoli in cardiomyocyte nuclei were reduced in newborn albino rats exposed to antennal hypoxia. All these changes developed against the background of oxidative stress. In mature animals, the absolute and relative heart weights were decreased, but the ratio of mononuclear cardiomyocytes in both ventricles was higher than in the control. These changes were accompanied by an increase in the percent of collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…IUH induces a decrease in the DNA-synthetic activity of CMC in the developing heart. We have previously shown that albino rats exposed to IUH had a reduction in the DNA-synthetic activity of CMC at the age of 1-day old [11]. In the current study, a similar effect was shown for 7-day old animals.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…IUH induces a decrease in the DNA-synthetic activity of CMC in the developing heart. We have previously shown that albino rats exposed to IUH had a reduction in the DNA-synthetic activity of CMC at the age of 1-day old [11]. In the current study, a similar effect was shown for 7-day old animals.…”
Section: Discussionsupporting
confidence: 87%
“…Administration of NALE peptide from the 2 nd through the 6 th days of life did not normalize gravimetric indices of experimental 7-day old animals. A decrease in gravimetric indices' values under the influence of IUH is formed in the antenatal period and is detected immediately after birth in 1-day old experimental rat pups [11]. In the current study, the introduction of the peptide in the neonatal period could not lead to the rapid restoration of body mass and heart mass of experimental animals.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…However, fetal hypoxia induced by placental embolization or placental restriction by removing maternal endometrial caruncles before conception decreased binucleation (113,596) and increased mononucleated cardiomyocytes (687) in fetal sheep. Intermittent maternal hypoxia increased the number of mononucleated cells by~150% in the left ventricle and~37% in the right ventricle of rats on postnatal day 60 (1171).…”
Section: Hypoxiamentioning
confidence: 98%